Analisis Masalah Pengaturan Ruang Udara Di Atas Alur Laut Kepulauan Indonesia (ALKI) - Dirwan, A (Jurnal Teknologi Kedirgantaraan, 2021)
United Nations Convention on the Law of the Sea 1982 (UNCLOS) was formed at 10 December 1982. Archipelagic State (Article 46) means a state constituted wholly by one or more archipelagos and may include other islands. Article 53, paragraph (2) UNCLOS 1982, stated: “all ships and aircraft enjoy the right of archipelagic sea lines passage in such sea lines and air routes”. However, this article could cause overlapping in applications, because ICAO already states all air areas in flight routes (ATS). In another article, the right of archipelagic sea lines passage, especially for military aircraft regarding the necessity to get permission from Archipelagic State, has been perceived differently by every states. This research with the grounded theory methode, involves expert respondents to see and synchronize few aspects or articles. Findings from this research are to complete the sentence of “all ships and aircraft enjoy the right of archipelagic sea lines passage .... “, with the understanding that all aircraft can provide overflight on archipelagic sea lines air area, which determined as an ATS route according to ICAO rules. Every military aircraft which uses the ATS route should have permission from Archipelagic State Goverment.